Self-assembly of lanthanide(iii) coordination polymers from a bifunctional 2-(pyridin-2-yl)-1H-imidazole-4, 5-dicarboxylate ligand with the assistance of oxalate: syntheses, structures, luminescence, and magnetic properties. Issue 14 (22nd March 2017) - Zhang, Li-Yang; Lu, Li-Ping; Zhu, Miao-Li; Feng, Si-Si
Abstract : Eleven lanthanide coordination polymers were prepared, with Eu(iii ) and Tb(iii ) complexes showing very strong reddish-orange and green emission bands, respectively. Abstract : Based on a bifunctional 2-(pyridine-2-yl)-1 H -4, 5-imidazole-dicarboxylic acid ligand, a novel family of lanthanide coordination polymers with formulas [Ln(HPIDC)(C2 O4 )0.5 (H2 O)] n (Ln = La, 1 ; Ce, 2 ) and [Ln2 (HPIDC)(C2 O4 )2 (H2 O)3 ] n ·2 n H2 O (Ln = Pr, 3 ; Nd, 4 ; Sm, 5 ; Eu, 6 ; Gd, 7 ; Tb, 8 ; Dy, 9 ; Ho, 10 ; Er, 11 ), (H3 PIDC = 2-(pyridine-2-yl)-1 H -imidazole-4, 5-dicarboxylic acid & H2 C2 O4 = oxalic acid) has been prepared under hydro-solvothermal conditions and characterized by single crystal X-ray diffraction, elemental analysis, IR spectroscopy, and thermogravimetric analysis. Notably, the ligands adopt the same μ3 -kN, O:kO′, O′′:kO′′′ conformation in all compounds, which brings about two types of isostructural lanthanide coordination polymers. Namely, 1 and2 crystallize in the monoclinic space group P 21 / n and are composed of [Ln2 (COO)2 ] dinuclear subunits with networks having the symbol (6 3 ·8 2 ·10)2 (6 3 )2 (8). Meanwhile, 3–11 crystallize in the monoclinic space group P 21 / c and are constructed with tetranuclear [Ln4 (COO)4 ] subunits with networks having the symbol (10 3 )2 (10 4 ·12 2 )(10)2 . The photoluminescence measurement indicates that Eu(iii ) and Tb(iii ) coordination polymers show very strong reddish-orange and green emission bands with CIE chromaticity coordinates (0.612, 0.325) and (0.284, 0.523) and quantum yields of 54.3% & 34.7%, respectively. The magnetic properties of3 and7–11 are investigated, and the results indicate a ferromagnetic interaction between Gd(iii ) magnetic centers in complex7 and antiferromagnetic interactions in other complexes.